Economic Evaluation of a Point-of-Care Test for Bacterial Vaginosis Among Women With Vaginal Symptoms. Issue 5 (11th May 2023) - Jiao, Boshen; Fredricks, David N.; Srinivasan, Sujatha; Hansen, Ryan
Abstract : This modeling study demonstrates that using a point-of-care test to diagnose bacterial vaginosis is likely to be cost-effective, especially with a high sensitivity or a substantial positive effect on productivity. Abstract : Background: There is an unmet need for a clinical diagnostic technology to detect bacterial vaginosis (BV) rapidly and accurately. Novel point-of-care (POC) tests have the potential to fulfill this gap. Our objective was to determine the cost-effectiveness of a hypothetical clinician-administered POC test for diagnosing BV in the United States. Methods: We developed a state-transition microsimulation model to evaluate the cost-effectiveness of using the POC test versus usual care among women of reproductive age with vaginal symptoms. We adopted a healthcare sector perspective that included relevant healthcare costs and a societal perspective that further incorporated productivity costs. Model parameters were empirically estimated based on commercial insurance claims data or derived from published literature. The primary model outcome was incremental cost-effectiveness ratio. We started with analyzing a hypothetical POC test with a sensitivity and specificity of 0.9 and a cost of 40, followed by extensive sensitivity analyses. Results: Using the hypothetical POC test to diagnose BV increased costs by 16 and quality-adjusted life-years by 0.0005 per person compared with the usual care, leading to an incremental cost-effectiveness ratio of 31, 108 per quality-adjusted life-year gained. When also capturing the productivity costs, the POC test resulted in an average cost savings of 57. The sensitivity analyses showed that the POC test's sensitivity was more influential on its cost-effectiveness than specificity. Conclusions: Using the POC test to diagnose BV is likely to be cost-effective relative to usual care, especially with a high sensitivity or a substantial positive effect on productivity.